2019
DOI: 10.4238/gmr18192
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Assessment of effects of the genetic polymorphisms on soccer athletes

Abstract: Several genes have been identified as important in athletic performance. The angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism has been related to improvements in performance and exercise duration. However, there are large divergences among studies on the influence of ACE I/D polymorphism on physical performance. Other studies have demonstrated that strenuous exercise generally overloads the endogenous antioxidant system's capacity, leading to oxidative damage to muscles and other tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, others failed to identify any significant relationship between ACE/ACTN3 polymorphisms and performance in young female football players [1]. Previous research suggests no association between the GSTM1/ GSTT1 polymorphisms and increased athletic performance [21]. Lastly, Dinc et al [22] found significant differences between the alleles of the MTHFR C677T polymorphism in terms of aerobic and anaerobic thresholds, favouring the CC allele.…”
Section: Endurancementioning
confidence: 97%
See 4 more Smart Citations
“…However, others failed to identify any significant relationship between ACE/ACTN3 polymorphisms and performance in young female football players [1]. Previous research suggests no association between the GSTM1/ GSTT1 polymorphisms and increased athletic performance [21]. Lastly, Dinc et al [22] found significant differences between the alleles of the MTHFR C677T polymorphism in terms of aerobic and anaerobic thresholds, favouring the CC allele.…”
Section: Endurancementioning
confidence: 97%
“…Endurance. The most studied polymorphisms were ACTN3 [1,15,20], ACE [20,21], AGT and AMPD [20], MTHFR [22], and GST [21]. Overall, 4 studies included young male football players and 1 involved youth female football players [1].…”
Section: Performancementioning
confidence: 99%
See 3 more Smart Citations